«Ambulant akutteam - Et sikkerhetsbelte for mennesker i psykisk krise?» - Monika Knudsen Gullslett; Bengt Karlsson; Ulla Forinder; Marit Borg (Septentrio Academic Publishing, 2014)
The objective of this study is to contribute with in-depth knowledge based on persons' subjective experiences within mental health crisis and support and help from a Crisis Resolution/Home Treatment (CR/HT) team. The study has a qualitative, exploratory design and qualitative interviews were conducted with seven persons. They have experiences with both inpatient treatment in hospitals and support from a CR/HT teams. The informants revealed a variety of experiences as service users in the different helping contexts. The experiences of the CR/HT team's accessibility, availability and flexibility, was highlighted as important.  The Service users felt they were taken more seriously and met as a fellow human being in the home setting as opposed to hospital ward. The informants also emphasized how the CR/HT team helped them to feel more safe and secure. This study offers some in-depth insights of being on the receiving end of mental health services. It is important to include experience based user knowledge in the evidence base of practice development.